15 Years of Small: Research Trends in Nanosafety. Issue 36 (27th April 2020) - Zhu, Shuang; Li, Lele; Gu, Zhanjun; Chen, Chunying; Zhao, Yuliang
Abstract: In the field of nano‐ and microscale science and technology, Small has become one of the worldwide leading journals since its initiation 15 years ago. Among all the topics covered in Small, "nanosafety" has received growing interest over the years, which accounts for a large proportion of the total publications of Small . Herein, inspired by its coming Special Issue "Rethinking Nanosafety, " a general bibliometric overview of the nanosafety studies that have been published in Small is presented. Using the data derived from the Web of Science Core Collection, the annual publication growth, most influential countries/institutions as well as the visualized collaborations between different countries and institutions based on CiteSpace software are presented. A special emphasis on the impact of the previous Special Issue from Small that is related to nanosafety research is given and the research trend from the most highly cited papers during last 15 years is analyzed. Lastly, future research directions are also proposed. Abstract : This Essay presents a general bibliometric overview of the nanosafety studies that have been published in Small . The publication trend regarding annual growth, most influential countries and institutions, and hot research topics in the "Nanosafety" field are listed and analyzed. At the end of this Essay, future research directions are also proposed.